2022
DOI: 10.3389/fnins.2022.1043446
|View full text |Cite
|
Sign up to set email alerts
|

Research advances in the application of vagus nerve electrical stimulation in ischemic stroke

Abstract: Stroke seriously endangers human well-being and brings a severe burden to family and society. Different post-stroke dysfunctions result in an impaired ability to perform activities of daily living. Standard rehabilitative therapies may not meet the requirements for functional improvement after a stroke; thus, alternative approaches need to be proposed. Currently, vagus nerve stimulation (VNS) is clinically applied for the treatment of epilepsy, depression, cluster headache and migraine, while its treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…Structural lesion is one of the most common causes of drug-resistant focal epilepsy ( 32 , 33 ). Recent studies have shown that VNS has neuroprotective effects in animal models of transient and permanent focal cerebral ischemia, which may be specifically related to mechanisms such as inhibition of apoptosis, mediation of angiogenesis, and protection of the blood-brain barrier ( 34 ). The protective mechanism of VNS against lesion in the brain may make it more effective against focal epilepsy than the generalized epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Structural lesion is one of the most common causes of drug-resistant focal epilepsy ( 32 , 33 ). Recent studies have shown that VNS has neuroprotective effects in animal models of transient and permanent focal cerebral ischemia, which may be specifically related to mechanisms such as inhibition of apoptosis, mediation of angiogenesis, and protection of the blood-brain barrier ( 34 ). The protective mechanism of VNS against lesion in the brain may make it more effective against focal epilepsy than the generalized epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been conducted on the application of VNS as a therapeutic option for several neurological conditions, including poststroke complications, for example, motor deficits, cognitive impairments, and mood disturbances. Emerging evidence supports the efficacy of VNS in facilitating poststroke motor recovery[ 30 ].…”
Section: Agus Nerve Stimulation For Strokementioning
confidence: 99%
“…Vagus nerve stimulation (VNS) regulates this pathway and promotes an anti-inflammatory phenotype post-stroke; it is approved for use in treatment-refractory epilepsy and has shown promise in the restoration of post-stroke upper limb function. 202,203 In a recent RCT, 108 ischemic patients with upper-limb motor dysfunction were randomly assigned to VNS (or control); 90 days after therapy, a clinically meaningful response was achieved in 47% of VNS patients, compared with 24% of controls, as measured on the Fugl-Meyer Assessment Upper-Extremity score (between-group difference: 24%, 95% CI: 6-41, p ¼ 0.0098). 204 Finally, FMT, or the transfer of intestinal bacteria/other microbes from a healthy donor to a post-stroke patient to restore a healthy microbiota, has been considered.…”
Section: Emerging Therapeutics In Stroke Targeting the Dysfunctional ...mentioning
confidence: 99%